Education to Develop Reading Literacy by Analyzing the Intrinsic Elements of Short Stories in Islamic Junior High School Students’ - Nugraha, Hilda Herliani; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2022)
We created a program to develop students’ reading literacy by analyzing the intrinsic elements of short stories. The method used is giving a pre-test, then giving material in the form of videos and power points, and post-test using 10 questions to 10 students’ of Islamic junior high school. The results of the pre-test showed that most of the students’ had answered correctly, with a score of 60%. The results of the post-test of students’ experiencing development are indicated by the achievement of a score of 90%. Students’ experienced an increasing scores because they had received the intrinsic elements of the short story before doing the post-test. The age of students’ does not affect the level of development of students’ in understanding the intrinsic elements of short stories. It is concluded that students’ can improve reading literacy by knowing how to analyze the intrinsic elements of short stories. Students’ can enjoy literacy activities by reading short stories by looking for intrinsic elements in the short stories they read. This program helps students’ in providing information about how to analyze the intrinsic elements of short stories so that they can help students’ develop in reading literacy activities.